Influências meteo-oceanográficas no padrão de distribuição espaço-temporal de concentração de clorofila-a na região do Embaiamento de Tubarão, Oceano Atlântico Oeste - Fernandes, Mahatma Soares (2015)
The region of Tubarão Bight (TB) is part of the Eastern Brazilian Shelf and has high ecological importance. The TB is characterized by the development of various small and mesoscale oceanographic features which contribute to the intrusion of the nutrient-rich South Atlantic Central Water (SACW) in the photic layer and thus promotes the development of phytoplankton blooms in different spatial and temporal scales. The present study investigates the spatial and temporal variability of chlorophyll-a concentration ([chl-a]) in the TB region in order to identify the main modes of variability and their relation with the physical water properties and meteorological forcing. For this purpose the following datasets have been used: eleven years (2003-2013) level 3 [chl-a] data from the Moderate Resolution Imaging Spectroradiometer (MODIS-Aqua), seven years (2005-2012) of model-derived meridional and zonal components of wind intensity INPE/ETA and thermohaline model results from the Global HYCOM 1/12° assimilation (HYCOM Consortium). The models results were validated by performing comparisons against thermohaline in situ data from ARGO buoys and CTD. The results show that the dominant patterns of [chl-a] distribution in TB can largely be interpreted in the context of two modes of spatio-temporal variability. The first mode is strongly linked to seasonal variations of the mixed layer depth in the oceanic region adjacent to the continental shelf, such as higher [chl-a] are associated with deeper mixed layer depth mainly during the winter season. On the continental shelf the same mode is also associated to changes in the wind intensity during spring. The second mode is of shorter duration than the first and takes place between November and January in a restricted area of the continental shelf and continental slope. This mode may be associated with the development of an upwelling process slightly north of 20°S promoted by the encroachment of the Brazil Current into the shelf break.